Altered intestinal microbiota in children with bronchiolitis - Wu, Xiao-bin; Wang, Jian; Tang, Yuan; Jiang, Jing; Li, Xue-mei (Frontiers in Microbiology, 2023)
Objective To investigate the correlation between the alteration of intestinal microbiota and disease in children with bronchiolitis. Methods 57 children diagnosed with bronchiolitis from January 2020 to January 2022 in our pediatric department were included as the case group, and another 36 normal children were included as the control group. Stool and blood were collected from both groups for high-throughput sequencing, untargeted metabolite detection and ELISA. A mouse model of RSV infection was established to validate the results of clinical case detection. Results Body weight , passive smoking , and a host of other factors were possible as acute bronchiolitis influencing factors in the onset of acute bronchiolitis. The alpha diversity Shannon, Simpson and Pielou's evenness indices were significantly lower in children with acute bronchiolitis than in healthy children with gated levels of Firmicutes, Bacteroidetes and genus levels of Clostridium and other short chain fatty acid-producing bacteria. The relative abundance of short-chain fatty acid (SCFAs)-producing bacteria decreased and the abundance of genus-level sphingolipid-producing bacteria Sphingomonas increased; the progression of acute bronchiolitis is likely to be associated with the abundance of Clostridium and Sphingomonas and higher fecal amino acid concentrations, including FF-MAS, L-aspartic acid, thioinosinic acid, picolinic acid; supplementation with Clostridium butyricum significantly alleviated RSV infection-induced lung inflammation. Conclusion The progression of bronchiolitis may be associated with altered intestinal microbiota, decreased SCFAs and elevated sphingolipids metabolism in children. Some fecal bacteria and metabolites may predict the onset of bronchiolitis, and oral administration of Clostridium butyricum may alleviate RSV infection-induced pulmonary inflammation.